Intrapartum cardiotocography with and without computer analysis: a systematic review and meta-analysis of randomized controlled trials. (2nd July 2020) - Campanile, Marta; D'Alessandro, Pietro; Della Corte, Luigi; Saccone, Gabriele; Tagliaferri, Salvatore; Arduino, Bruno; Esposito, Giuseppina; Esposito, Francesca Giovanna; Raffone, Antonio; Signorini, Maria Gabriella; Magenes, Giovanni; Di Tommaso, Mariarosaria; et al.
Abstract: Objective: To evaluate whether intrapartum cardiotocography with computer analysis decreases the incidence of newborn metabolic acidosis or obstetric intervention when compared with visual analysis through a systematic review with meta-analysis of randomized controlled trials. Methods: The research was conducted using Medline, Embase, Web of Science, Scopus, ClinicalTrial.gov, Ovid and Cochrane Library as electronic databases from the inception of each database to May 2018. Selection criteria included randomized trial evaluating women with cephalic presentation at term or late preterm term during labor who were randomized to electronic fetal heart rate monitoring with either computer analysis (i.e. intervention group) or standard visual analysis (i.e. control group). Trials evaluating antenatal fetal heart rate monitoring in women not in labor were excluded. The primary outcome was incidence of newborn metabolic acidosis, defined as pH less than 7.05 and base deficit greater than 12 mmol/L. Secondary outcomes were mode of delivery, admission to neonatal intensive care unit, hypoxic–ischemic encephalopathy, and perinatal death. The summary measures were reported as relative risk (RR) with 95% confidence interval (CI). Results: Three randomized controlled trials (RCTs), including 54, 492 participants, which met inclusion criteria for this meta-analysis, were analyzed. All the included trials enrolled women with cephalic presentation at term or late preterm. Women were randomized in the active first stage of labor and all of them received continuous cardiotocography (CTG) from randomization until delivery. Women who received continuous CTG during labor with computerized analysis had similar risk of newborn metabolic acidosis. No between group differences were found in the secondary outcomes. Conclusions: Compared with visual analysis, use of computer analysis of fetal monitoring signals during labor did not significantly reduce the rate of metabolic acidosis or obstetric intervention.